E-Banking Technology Characteristics and Performance of Micro and Small Enterprise in Kenya: A Moderated Mediation Model of Adoption and Innovative Behavior - Kitigin, Beatrice; Korir, Michael; Chepkwony, Kefa (SEISENSE (PRIVATE) LIMITED, 2021)
Purpose- The study investigated the indirect effect of innovative behavior on the relationship between e-banking technology characteristics and micro and small enterprises (MSE) performance through e-banking technology adoption in Kenya. Design/methodology: The study employed an explanatory research design and a multistage sampling technique to collect cross-sectional data using a self-administered questionnaire. The sample size of 455 MSEs was drawn from a target population of 5915 in Vihiga County, Kenya. Findings-The study findings showed a complementary mediation of e-banking technology adoption on the relationship between e-banking technology characteristics and MSE performance. Additionally, innovative behavior moderated the association between e-banking technology adoption and MSE performance but did not moderate the relationship between e-banking technology characteristics and e-banking technology adoption. Further, innovative behavior moderates the indirect relationship between e-banking technology characteristics and MSE performance via e-banking technology adoption. This effect was much more substantial, with a higher level of innovative behavior. Practical Implications- These findings underscored the need for policy reviews for government, county, and private sector on e-banking technology adoption and MSE performance in Kenya. Originality/value- The study's findings bring vital knowledge concerning the indirect effect of e-banking technology adoption and innovative behavior on the study variables.